2018
DOI: 10.1155/2018/1813047
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Role of Trace Elements in IBD

Abstract: Micronutrient deficiencies are common in inflammatory bowel disease and have clinical impact, being both a sign of complicated disease and a cause of morbidity. The involved systemic inflammatory response is responsible for altering the concentration of a wide range of trace elements in the serum, including zinc and selenium. This review summarizes recent advances and evidence-based knowledge regarding the impact of selenium and zinc on oxidative stress and microbiota changes in IBD patients. Getting new insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 96 publications
1
29
0
Order By: Relevance
“…28 These previous studies are reminiscent of the findings described here for Mn, as deficiencies in these other trace minerals also show effects on the intestinal barrier and immune functions. 25 One striking feature of Mn deficiency was its impact on the severity of DSS-induced colitis. Previous studies using Se-deficient diets (<0.01 mg/kg) showed that a time period of 12 weeks was required before Se deficiency resulted in any worsening in the colons of DSS-induced colitis in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 These previous studies are reminiscent of the findings described here for Mn, as deficiencies in these other trace minerals also show effects on the intestinal barrier and immune functions. 25 One striking feature of Mn deficiency was its impact on the severity of DSS-induced colitis. Previous studies using Se-deficient diets (<0.01 mg/kg) showed that a time period of 12 weeks was required before Se deficiency resulted in any worsening in the colons of DSS-induced colitis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Micronutrient deficiencies have been, for decades, a major concern in the management of IBD as numerous studies have documented associations between IBD and deficiencies in trace minerals, such as Fe, Zn, and Se. 25 Fe deficiency is associated with the bleeding, malabsorption, or anemia that occurs in one-third of IBD patients, 26 while zinc deficiency is also common in patients with IBD (15 to 40% of the patient population). 27 Similarly, an inverse association has been reported for nutritional Se status and the occurrence of IBD.…”
Section: Discussionmentioning
confidence: 99%
“…IBD is characterized by ongoing chronic inflammation, which generates, among others, oxidative stress. Selenium deficiency has been demonstrated during both exacerbation and remission in patients with UC and CD [83]. Researchers describe selenium deficiencies in patients with CD, which may lead to the reduction of the body's immune response to the development of inflammation.…”
Section: Zinc Zinc Is a Food Component Classed As A Micronutrientmentioning
confidence: 99%
“…Of those, however, Cu and Fe, if not protein-bound, interact with hydrogen peroxide and produce hydroxyl radical in Fenton reaction, exacerbating rather than attenuating the oxidative stress. Accordingly, an increased Cu/Zn ratio accompanies inflammatory and oxidative stress conditions [79]. Although the evidence on the role of micronutrients in the pathogenesis of IBD is limited, two large prospective studies have demonstrated that zinc intake is associated with decreased risk of CD but not UC [80].…”
Section: Diagnostic Markers In Ibd (Markers Not Specific For Either Umentioning
confidence: 99%
“…Malnutrition accompanying some IBD patients, particularly those with CD, may either cause or exacerbate the existing deficiencies. Indeed, the estimates on the prevalence of zinc deficiency among IBD patients differ from 14% to even 40% [79]. Our literature screening retrieved only a few papers, in which Se and Zn have been assessed.…”
Section: Diagnostic Markers In Ibd (Markers Not Specific For Either Umentioning
confidence: 99%